A meta-analysis investigating incidence and features of stroke in HIV-infected patients in the highly active antiretroviral therapy era. Issue 12 (December 2015) - D'Ascenzo, Fabrizio; Quadri, Giorgio; Cerrato, Enrico; Calcagno, Andrea; Omedè, Pierluigi; Grosso Marra, Walter; Abbate, Antonio; Bonora, Stefano; Biondi Zoccai, Giuseppe; Moretti, Claudio; Gaita, Fiorenzo
Abstract : Objective: Recent studies have suggested a close biological and clinical association between HIV infection and risk of myocardial infarction, whereas contrasting data have been reported about incidence of stroke and its clinical predictors. Design and setting: Studies including HIV-infected patients developing a cerebral ischemic event were systematically searched for in MEDLINE/PubMed. Patients and main outcome measures: Baseline, treatment and outcome data were appraised and pooled with random-effects methods computing summary estimates (95% confidence intervals). Results: Five studies comprising 89 713 participants were included: they were young [46 (46–50) years, mainly male (70% (68–79)] with a moderate prevalence of diabetes [19% (14–21)]. Atrial fibrillation and history of previous coronary artery disease were observed in 3% (2–5) and 18% (15–22), respectively. All patients were on highly active antiretroviral therapy (HAART) and had been treated for a mean of 5 (2–6) years. After a median of 4 (3–5) years of follow-up, 1245 ischemic strokes occurred [1.78% (0.75–2.81)]. Traditional risk factors such as age (five studies), hypertension (three studies), smoking (two studies), hyperlipidemia (one study), atrial fibrillation (one study) and diabetes (one study) were identified as independent predictors of stroke. In one study, RNA viral load [log of odds ratio = 1.10 (1.04–1.17)] and CD4+ cell count less than 200/μl were clinically related to stroke, whereas HAART therapy showed a neutral effect. Conclusion: Stroke represents a relatively common complication in young, HAART-treated HIV patients. Apart from traditional cardiovascular risk factors, HIV-RNA viral load may help to target and manage patients at risk.